The Impact of the Participation in Decision Making on the Organization Creativity (Al-Mansour Journal, 2025)
The research aims to study the impact of workers\\' participation in decision-making on the organizational creativity of the University of Baghdad, where the study was applied to a random sample of (384) Discussed, relied on descriptive analysis and standard analysis using the linear regression model to study the impact of workers\\' participation on organizational creativity and reached several findings, the most important of which is that the University still does not give lower departments substantial decision-making powers; Participatory thinking in decision-making remains limited and the University\\'s levels of organizational creativity are moderate. The results of the linear regression analysis also showed a strong correlation and high moral impact that reached 82% between the involvement of workers in decision-making and organizational creativity at the university. The study recommended that the University should give greater attention to lower-level departments with some capabilities that have creative and innovative thinking and are capable of developing the University\\'s performance, Enhancing channels of communication and participation between different departments and their employees and the need to promote and motivate those with creative and innovative ideas and entrepreneurs to promote participatory thinking in decision-making that would stimulate a qualitative shift in the University\\'s performance due to its wide impact on both the staff and the departments at all levels.
Keywords: decision-making,Workers’ Participation,Organizational Creativity.